Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja Pegawai pada PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Depok - Iren Mailuhu; Nurlaela Eva Puji Lestari; Sudirja Sudirja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Iren Mailuhu (64210645), The Influence of Competency and Work Discipline on Employee Performance at PT. PLN (Persero) Customer Service Implementation Unit (UP3) Depok PT. PLN (Persero) PT. PLN (Persero) is a company owned by the state. The task of this company is to provide electricity distribution services and organize its main service units into several parts that are appropriate to the electric power system, such as generation, transmission and distribution. PT. PLN (Persero) in managing human resources needs to pay attention to the competency and work discipline of each employee in order to produce employees who are of good quality and superior performance. This research aims to determine the influence of competence and work discipline on employee performance at PT. PLN (Persero) Customer Service Implementation Unit (UP3) Depok. The research method used is a quantitative method with data collection using saturated samples or non-probability sampling. A total of 56 respondents were sampled and the data obtained was processed using SPSS version 27 with multiple linear regression analysis techniques, The results of the analysis show that Y = 6.651, X1 = 0.625, Based on the coefficient of determination test, it was found that the two independent variables had an influence of 68.1% on employee performance.